ECOMASJID: THE FIRST MILESTONE OF SUSTAINABLE MOSQUE IN INDONESIA - Hidayat, Eka Rahmat; Danuri, Hasim; Purwanto, Yanuar (Journal of Islamic Architecture, 2018)
On November 11, 2017, MUI (Indonesian Council of Ulama), DMI (Indonesian Mosque Council) have launched the national program named eco masjid. Eco masjid is a program of sustainable mosque through efforts to preserve the environment and natural resources oriented to on aspects of idarah (management), imarah (prosperity activities), and ri’ayah (maintenance and facilities) which dominantly related to its building. In Indonesia, sustainable building principles are widely promoted by GBCI (Green Building Council Indonesia) and have been applied to various types of buildings. However, it has been realized that the study on the implementation of sustainable principle in the mosque is very rare. The research was carried out qualitatively by using direct observation on the pilot mosque to capture all implemented sustainable building principle. Based on the questionnaire to 44 participants which reflected 44 DKM (Dewan Kemakmuran Masjid), the result came up that applying water efficient faucet, using the LED lamp and sticker posting are the most achievable sustainable practices in the existing mosques. The authors suggest to all related bodies to determine the standard on how to assess the implementation of eco Masjid program